Street Art and related terms: discussion and working definition - Blanché, Ulrich (Street Art & Urban Creativity, 2015)
This paper gives a short introduction and discussion of the term Street Art and related terms like Graffiti and Urban Art. A major part discusses my definition of Street Art and other definitions and the differences and commonalities of these terms. Street Art consists of self-authorized pictures, characters, and forms created in or applied to surfaces in the urban space that intentionally seek communication with a larger circle of people. Street Art is done in a performative and often site-specific, ephemeral, and participatory manner. Street Art is mostly viewed online. It differs from Graffiti and Public Art. I quote first and foremost German researchers that are not translated into English but in my opinion should be part of the international academic discussion